Increasing MSME Performance Through Institutional Strengthening, Entrepreneurship, and Digital Marketing - Rini Tresnasari; Zulganef Zulganef (International Journal of Research in Community Services, 2023)
The Indonesian economy currently lack of solid fundamentals, which has prompted the government to continue strengthening Micro, Small, and Medium Enterprises (MSMEs). This industry can support the government and take on a sizable workforce. MSMEs have demonstrated they can survive and grow into the engine of the economy, especially after the financial crisis, so their survival cannot be questioned. MSMEs contribute 61.1% of the national economy's Gross Domestic Product (GDP) and can absorb productive labor in Indonesia. MSMEs must be able to maintain MSME performance, survive with all their available resources, and even experience growth in this uncertain situation. Some of the issues MSMEs encounter include the lack of legal institutions. MSMEs need legal institutions because they can boost consumer confidence in the products they sell. The second issue is the change in pandemic consumer trends from offline to online for products and services. In order to maintain MSME performance under unpredictable circumstances, particularly those caused by external environmental factors, Entrepreneur Marketing (EM) is a conceptual approach that is ideal for implementation in MSMEs. The conventional marketing idea, which served as a business solution, has been replaced by the idea of entrepreneurial marketing. In order to increase MSME performance, MSMEs must also benefit from digital marketing, which tries to market through digital media to reach target consumers swiftly and precisely. This study highlights the issues that MSMEs face and how to enhance institutions, encourage entrepreneurship, and use digital marketing to improve MSME performance.